Stigma Masyarakat Terhadap Anak Berkebutuhan Khusus Di Sekolah Umum - Eka Mayang Sari; Opi Andriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article aims to determine the public stigma towards children with special needs in public schools. This research uses a qualitative descriptive research method. Data collection techniques include: observation, interviews, and documentation. The research subjects or informants are the surrounding community. The results of the research show that the public's stigma towards children with special needs in public schools is relatively good, as according to the results of interviews, the community understands well enough about the characteristics of children with special needs in the learning and interaction process. The learning process for children with special needs is the same as for children in general, namely preparing lesson plans as learning planning, using strategies, methods and various media for implementing learning, as well as evaluating learning. It's just that the learning process carried out is adaptive, meaning that the learning process adapts to the students' own circumstances. Children who have special needs (ABK) generally have obstacles and difficulties in communicating verbally with other people